O uso de vídeos em aulas de Química - Leandro Henrique Fantini (2016)
The goal of this work was to share investigations made about the possible uses of video in science education, especially in chemistry teaching. In particular, we try to think how the science teacher can use scientific videos in his practice. There are many kinds of videos that can be used in the classroom. We created categories that may help the teacher to recognize the purpose and the way he can use this resource in the classroom and that can contribute to a better understanding of the possible uses of videos by him and his students. Some categories identified by us were: I) videos of experiments, II) videos as tutorials for the teacher, III) videos that allow data collection, IV) linked videos, V) contextualized videos. We present examples of videos of each category, by selecting materials already published and, in some cases, unique video productions prepared exclusively for this work. The study highlights the importance of video in chemistry lessons and brings some Internet portals that have a large collection of resources that can be accessed by students and teachers. It is hoped that this material, along with the book, which was published together with this dissertation can help teachers with the most appropriate choice of a video for its class.